2021
DOI: 10.47197/retos.v0i41.83455
|View full text |Cite
|
Sign up to set email alerts
|

Combining Physical Education and unstructured practice during school recess to improve the students’ decision-making and execution (Combinando las clases de Educación Física con práctica no estructurada durante los recreos para aumentar la toma de decisi

Abstract: The purpose of this study was to analyze the effect of a unit of basketball based on Teaching Games for Understanding model combined with a program of unstructured practice based on small-sided games (experimental group), in comparison to the only application of the unit (control group), on the decision-making and execution in Physical Education students. Participants were 31 students with ages between 12 and 14. The intervention was conducted over four weeks, developing eight PE lessons and eight schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(64 reference statements)
0
3
0
3
Order By: Relevance
“…and FT for the EG. Despite the absence of significant differences between pre-and post-training in 2P shooting performance, the EG showed gains of 14.40% at the end of the training program, supporting the positive effect of the extra practice time on skill execution (Práxedes, González, del Villar & Gil-Arias, 2021). On the other hand, the effects of the training program on the ball release parameters (RH, RA and RS) and on the TV deserve the following comments:…”
Section: Discussionmentioning
confidence: 82%
“…and FT for the EG. Despite the absence of significant differences between pre-and post-training in 2P shooting performance, the EG showed gains of 14.40% at the end of the training program, supporting the positive effect of the extra practice time on skill execution (Práxedes, González, del Villar & Gil-Arias, 2021). On the other hand, the effects of the training program on the ball release parameters (RH, RA and RS) and on the TV deserve the following comments:…”
Section: Discussionmentioning
confidence: 82%
“…Regarding decision-making, carried out an eight-week 3 vs. 3 SSGs intervention with school girls and observed an improvement in decision-making. Similarly, in the school setting, Práxedes et al (2021) demonstrated enhanced decision-making among Physical Education students following a four-week SSG intervention. In another study, Tallir et al (2012), compared the 5 vs. 5 and 3 vs. 3 SSGs formats and found that the 3 vs. 3 improved decision-making and action execution efficiency compared to the 5 vs. format.…”
Section: Tactical-technical Behaviormentioning
confidence: 89%
“…Participants ranged from 8-year-old beginners (Martínez-Fernández et al, 2015) to senior players at the professional level (Boros et al, 2020;Brini et al, 2021). The game format manipulations ranged from 1 vs. 1 (Clemente et al, 2021b;Clemente et al, 2019;Clemente et al, 2020b;González-Espinosa et al, 2021) to 5 vs. 5 (Clemente et al, 2021b;Clemente et al, 2017;Clemente et al, 2019;Clemente et al, 2020b;Ferioli et al, 2020;Figueira et al, 2022;Köklu et al, 2017;Mateus et al, 2019;McCornick et al, 2012;Piñar et al, 2009;Práxedes et al, 2021;Tallir et al, 2012). The characteristics of the studies included in this review, along with specific instruments and results related to the tactical and technical variables, are available in Table 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…grado básico de Chile encontraron una relación entre todas las variables de la condición física con las variables del rendimiento escolar en la materia de matemáticas (Otero & Lafuente Fernández, 2022). De igual forma, el pre-experimento que se realizó de activación física matutina poseía una duración diaria de 30 minutos previo a la jornada escolar y se encontraron cambios significativos de algunas materias, en ese sentido, se han observado en algunas investigaciones, una relación positiva entre una hora de actividad física con la mejora de las calificaciones escolares y con ello un aumento del rendimiento escolar (Dwyer et al, 2001& Lankhorst et al, 2015 por lo que se pudiera aumentar la duración de la activación o agregar otro momento donde se realice este programa, como son los recesos escolares o en las clases de educación física para producir beneficios en la función cognitiva, la función ejecutiva y el rendimiento académico (Lomas Rivera & Clemente Remón, 2017;Práxedes et al, 2021).…”
Section: Discussionunclassified